Analisis Intensitas Energi Listrik dalam Menghemat Penggunaan Listrik di Fakultas Teknik UNG - Sardi Salim; Ade Irawaty Tolago; Maharani R.P. Syafii (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
The electrical energy use in government buildings seems to pay less attention to electrical energy-saving provisions. Many rooms still have the lighting on during the day although the room has enough of sunlight. Using many air conditioners (AC) does not comply with the room volume and the number of people in the room. It leads to electrical energy waste, which is a problem at Universitas Negeri Gorontalo (UNG). The UNG household has reported that the electricity consumption in March 2021 was 65,291,330 VA. It greatly burdened the university’s operating costs budget (±60.30% of UNG’s household operating funds). This study aims to analyze the electrical energy use intensity and establish electrical energy use saving policies. The study was conducted at the Faculty of Engineering of UNG. The employed research method was the audit analysis of energy use intensity (EUI). The room lighting level according to the lighting and sunlight entering the room was directly measured with a lux meter and analyzed following the provisions of Indonesian National Standard (Standar Nasional Indonesia, SNI) 6197-2011. Electrical energy use in air-conditioned and non-air-conditioned rooms was analyzed using the EUI method. The energy use level refers to efficiency standards following the Regulation of the Minister of Energy and Mineral Resources No. 13 of 2012. The results showed that, on average, 23.43% of the 233 rooms had lighting intensity exceeding the SNI standard. The electrical power use in an air-conditioned room for 26 working days was 14.73 kWh/m2/mo. Based on the efficiency standards of the Minister of Energy and Mineral Resources Regulation, it falls into the moderately wasteful category. Electrical energy saving is conducted by implementing the room lighting system efficiency, and the use of AC with power complies with the standards of room coolness demands and the implementation of electrical energy saving life patterns.